Prospective, randomized, double-blind, double-dummy, active-controlled, phase 3 clinical trial comparing the safety and efficacy of intranasal dexmedetomidine to oral midazolam as premedication for propofol sedation in pediatric patients undergoing magnetic resonance imaging: the MIDEX MRI trial - Olivia Nzungu Wabelo; Denis Schmartz; Mario Giancursio; Françoise De Pooter; Giulia Caruso; Jean-François Fils; Philippe Van der Linden (Trials, 2023)
Abstract Background Children under 6 years who need magnetic resonance imaging usually require sedation to obtain best quality images, but the optimal sedation protocol remains to be determined. In 2018, we showed a 22% interruption in image acquisition during magnetic resonance imaging when performing a propofol-based sedation using a bolus approach. As non-pharmacological premedication is often insufficient to reduce the anxiety of children related to parental separation, pharmacological premedication may be useful to facilitate the induction of anesthesia. In our institution, effective premedication is obtained oral intake of midazolam, though its administration relies on patients’ compliance and could also lead to paradoxical reaction. Dexmedetomidine has a safe profile in the pediatric population and can therefore represent an interesting alternative. The primary objective of this trial is to demonstrate the superiority of intranasal dexmedetomidine compared to oral midazolam as premedication in reducing the occurrence of any event requiring temporary or definitive interruption of the examination to allow anesthesiologist intervention in children undergoing magnetic resonance imaging under propofol sedation. Methods In this single-center, prospective, randomized, double-blind, double-dummy, active comparator-controlled, superiority trial, we planned to include 250 patients, aged 6 months to 6 years, undergoing a scheduled magnetic resonance imaging requiring the presence of an anesthesiologist. After informed consent, the patients will be randomized to receive either oral midazolam or intranasal dexmedetomidine as premedication. The data will be analyzed in intention to treat, using Kolmogorov–Smirnov Z, chi-square, Wilcoxon, and Mann–Whitney U tests. A P-value < 0.05 will be considered statistically significant. Discussion The MIDEX MRI study will assess the efficacy of intranasal dexmedetomidine compared to oral midazolam to improve the quality of a propofol-based sedation prior to magnetic resonance imaging, without negative repercussion on the postoperative period. Trial registration ClinicalTrial.gov NCT05192629 . Registered on 14 January 2022. Protocol version 2.1